(3GdCSS GdfXQjI h GdWQGFb GdcejIs - (3cGSQ fUQ(B, (3GdefUhQs ((3YeGf(B:s (3GdMGeO(B,s, 2010)
(3eaghe GOGQI GdYedjGJ h GdJWhQ GdJGQjNj dgG , eGgjI hXjaI GdGfJGL , JfXje GOGQI GdedjGJ aj GdefXeI , fXQjI GdGfJGL h GdJcGdja , JcfhdhLjG GdGfJGL , GdHQeLI GdNWjI (B: (3GdfeGPL GdYGeI , eSGFd Gdfbd h eSGFd GdJNUjU , JUeje GdefJL h JWhjQg , GNJjGQ ehbY GdJSgjdGJ h GdJOQjH GdOGNdj dgG , GdJNWjW GdYedjGJj ddSjWQI Ydi GdhbJ h GdJcGdja , GbJUGOjGJ hbJ GdYed (B( (3JUeje fXGe GdYed(B) (3, LOhdI GdGfJGL h LOhdI GdYedjGJ , GdJNWjW GdGLeGdj eY hLhO CSFdI h eSGFd aj fgGjI cd aUds
Keywords: (3EOGQI GdGYeGds; (3GdGfJGLs; (3HMhK GdYedjGJs